Microenergy acoustic pulses promotes muscle regeneration through in situ activation of muscle stem cells. Issue 7 (17th October 2021) - Zhang, He; Kim, Hubert T.; Feeley, Brian T.; Lin, Guiting; Lue, Tom F.; Liu, Mengyao; Banie, Lia; Liu, Xuhui
Abstract: Microenergy acoustic pulses (MAP) is a modified low‐intensity extracorporeal shock wave therapy that currently used for treating musculoskeletal disorders. However, its function on muscle regeneration after ischemia‐reperfusion injury (IRI) remains unknown. This study aimed to explore the effect of MAP on muscle injury after IRI and its underlying mechanisms. Ten‐week‐old C57BL/6J mice underwent unilateral hindlimb IRI followed with or without MAP treatment. Wet weight of tibialis anterior muscles at both injury and contralateral sides were measured followed with histology analysis at 3 weeks after IRI. In in vitro study, the myoblasts, endothelial cells and fibro‐adipogenic progenitors (FAP) were treated with MAP. Cell proliferation and differentiation were assessed, and related gene expressions were measured by real‐time PCR. Our results showed that MAP significantly increased the muscle weight and centrally nucleated regenerating muscle fiber size along with a trend in activating satellite cells. In vitro data indicated that MAP promoted myoblast proliferation and differentiation and endothelial cells migration. MAP also induced FAP brown/beige adipogenesis, a promyogenic phenotype of FAPs. Our findings demonstrate the beneficial function of MAP in promoting muscle regeneration after IR injury by inducing muscle stem cells proliferation and differentiation.